Propuesta de mejora en la gestión de mantenimiento y logística para incrementar la rentabilidad de una empresa de transportes de carga ubicada en la ciudad de Trujillo 2021 - Bereche Meneses, Cecybell (2022)
The general objective of this work is to apply the proposal for improvement in the maintenance and logistics management of a transport company through the use of industrial engineering tools to increase profitability, whether due to poor logistics management, preventive maintenance plan, bad location of the mobile support and lack of order in the warehouse. Once the problem, objectives, hypotheses and variables were raised, maintenance and logistics management was used, in which tools such as reorder point, minimum stock, lead time, preventive maintenance plan, Weber and ABC were applied, said proposals for improvement were applied to each of the root causes presented by the company through the Ishikawa diagram, focusing on those that have the greatest impact on the profitability of the company with a total of 4. The improvement proposals were based on the implementation of tools of industrial engineering which allowed to eliminate or reduce activities that did not generate any value for the company causing customer dissatisfaction. Implementing these improvements, a total profit of S/50,839.28 would be obtained. The NPV was S/8,143. The IRR, 60.754%; The Benefit-Cost 1.70 and the Investment Return Period (PRI), 7 months. These indicators demonstrate the desirability of the proposal.